The relationship between previous antimicrobial use, antimicrobial resistance and treatment outcome among Alaskans treated for Helicobacter pylori infection. Issue 4 (5th July 2019) - Bruce, Michael G.; Bruden, Dana; Newbrough, Deidra; Hurlburt, Debby A.; Hennessy, Thomas W.; Morris, Julie M.; Reasonover, Alisa L.; Sacco, Frank; McMahon, Brian J.
Summary: Background: Helicobacter pylori isolates from Alaska have demonstrated a high prevalence of antimicrobial resistance. Objectives: To determine treatment failure in three groups, and analyse the relationship between treatment failure and antimicrobial resistance. Methods: Antimicrobial susceptibility was determined using agar dilution and Etest. Treatment success was determined using the urea breath test 2 months after antimicrobial therapy. Results: Among 303 treated adult patients, 103 (34%) failed initial treatment despite a 91% compliance with medication. About 222 (73%) patients were treated with a clarithromycin‐based regimen, 55 (18%) with a metronidazole‐based regimen, 15 (5%) with a regimen that contained clarithromycin and metronidazole and 11 (4%) with other antimicrobials. Among 260 culture‐positive patients, 156 (60%) were infected with metronidazole‐resistant isolates, 74 (28%) clarithromycin‐resistant, 52 (20%) clarithromycin/metronidazole‐resistant, 40 (15%) levofloxacin‐resistant, 11 (4%) clarithromycin/metronidazole/levofloxacin‐resistant and nine (3%) amoxicillin‐resistant. Overall, 34% of patients were treated with at least one antibiotic to which their infecting organism was resistant. Among patients treated with clarithromycin‐based regimens, treatment failed in 72% of patients carrying clarithromycin‐resistant H pylori vs 20% with clarithromycin‐sensitive strains (RR = 3.7, P < 0.001). Among patients treated with metronidazole‐based regimens, treatment failed in 19% of patients carrying metronidazole‐resistant H pylori vs 24% with metronidazole‐sensitive strains ( P = 0.72). Conclusions: A high proportion of H pylori isolates demonstrate resistance to clarithromycin, metronidazole or levofloxacin. Over one third of H pylori ‐infected patients were treated with an antibiotic to which their infecting organism demonstrated resistance. Clarithromycin resistance is associated with a greater risk for failure with clarithromycin‐based multidrug regimens compared to clarithromycin‐sensitive; resistance to metronidazole did not affect treatment failure.